Short-acting hormonal contraceptive continuation among low-income postpartum women in Texas - Kristen Lagasse Burke; Lauren Thaxton; Joseph E. Potter (Elsevier, 2021)
Objective: The objective was to assess continuation of the pill, patch, ring or injectable (i.e., short-acting hormonal contraception); characteristics associated with discontinuation; and subsequent method use among low-income postpartum women in Texas. Study design: Using a 24-month cohort study of 1700 women who delivered in eight Texas hospitals and were uninsured or publicly insured at the time of delivery, we focused on 456 women who used short-acting hormonal contraception within 6 months after delivery. We classified this sample according to characteristics and method preference, and estimated rates of discontinuation and associated predictors using life tables and Cox models. We assessed reasons for discontinuation and subsequent contraceptive use among those who discontinued. Results: Roughly half used the pill and half used the injectable. One hundred seventy-eight (39%) expressed a baseline preference for the method they used, 162 (36%) preferred a long-acting reversible contraception method, and 41 (9%) preferred sterilization. After 1 year, 72% had discontinued [95% confidence interval (CI) 67.1-75.7]. Foreign-born Hispanic women were less likely to discontinue than U.S.-born Hispanics [adjusted hazard ratio (aHR), 0.65; 95% CI 0.50-0.84]. Those who wanted a more effective method (aHR, 1.44; 95% CI 1.12-1.85) and those who lost insurance coverage (aHR, 1.47; 95% CI 1.12-1.92) were more likely to discontinue. The most common reasons for discontinuation were side effects and access/cost. Of those who discontinued, 243 (68%) switched to a less effective or no method. Only 47 (13%) switched to their preferred method. Conclusions: Short-acting hormonal contraceptive discontinuation is high in this population. Many switch to less effective methods after discontinuation despite preferring methods at least as effective as the pill, patch, ring or injectable. Implications: Expanding contraceptive coverage in the 2 years after delivery should be a state and federal policy priority. In clinics, providers should discuss contraceptive preferences throughout pregnancy and the interpregnancy interval.